Profil Literasi dan Perilaku Keuangan Mahasiswa Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar - Krisdayanthi, Astrid; Wulandari, Putu Riska; Kristina, Ni Made Rai; Premananda, Ni Luh Putu Uttari (Ekuitas: Jurnal Pendidikan Ekonomi, 2024)
The financial literacy of Indonesian society is still low. Financial literacy is certainly correlated with financial behavior. This study aims to analyze the financial literacy and behavior of students of the Dharma Duta Faculty of I Gusti Bagus Sugriwa Hindu State University, Denpasar. This study is included in quantitative descriptive research. The research instruments are financial literacy tests and financial behavior questionnaires. Data were analyzed quantitative descriptively. The results of the research state that: 1) the financial literacy level of students at the Dharma Duta Faculty of I Gusti Bagus Sugriwa State Hindu State University, Denpasar is in the medium category and 2) the financial behavior of students at the Dharma Duta Faculty of I Gusti Bagus Sugriwa Hindu State University, Denpasar is in the high criteria.